HARMONISASI HUKUM POSITIF DAN HUKUM ISLAM DI PENGADILAN AGAMA - Dini Hawa Yuswanti; Zatmiana Sukardi (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2026)
The harmonization of positive law and Islamic law in Religious Courts is a fundamental issue in Indonesia's pluralistic national legal system. This study aims to analyze the concepts, practices, and models for synchronizing these two legal systems in recognizing Religious Courts. This study uses a normative legal research method (normative juridical) with a regulatory, conceptualization, and case study approach. The legal sources used include primary legal materials in the form of regulations and court decisions, secondary legal materials in the form of scientific works and legal journals, and tertiary legal materials. The results indicate that the harmonization of positive law and Islamic law in Religious Courts has occurred through three main mechanisms: the positivization of Islamic law through legislation, judicial interpretation through rechtsvinding, and the formation of jurisprudence by the Supreme Court. However, normative conflicts persist, particularly in the areas of interfaith marriage and inheritance for non-Muslim heirs. This study recommends an integrative synchronization model that combines conceptual, normative, and practical solutions through strengthening the provisions of the Compilation of Islamic Law, regulatory reform, and increasing the capacity of judges to make progressive legal discoveries